Evaluation of Vegetable Oils and Their Respective Fatty Acids on the Viability of Streptococcus Mutans, a Persistent Oral Pathogen - Hughes, P.I; Kealey, C; Rowan, N.J; Brady, D.B (Journal of Asian Scientific Research, 2013)
This study evaluated the in vitro antibacterial activity of vegetable oils and their respective fatty acid constituents on the growth of Streptococcus mutans. S. mutans is one of the primary etiological agents associated with the onset of dental caries, a disease which is considered to be an oral health epidemic in industrialized countries. Micro-broth dilution assays were carried out to assess the viability of the oral pathogen in the presence of olive oil, palm, oil, sunflower seed oil and coconut oil. Bacterial growth was not affected by any of the oils tested. A selection of MCFAs and LCFAs comprising capric, lauric, myristic, oleic and linoleic acid showed varying levels of bacteriostatic activity towards S. mutans, wherein lauric acid was the most effective MCFA and linoleic acid the most effective LCFA. The findings of this study indicate that vegetable oils tested do not directly inhibit the viability of S. mutans. The fatty acid content in these oils are present as triglycerides but when in free form do exact an inhibitory effect.